The Impact of Regular Exercise on Cardiovascular Health: A Literature Review - Sari, Liliana Puspa; Karo Karo, Alan Alfiansyah Putra; Keliat, Pedomanta; Abady, Andi Nur; Nugroho, Agung; Syaleh, Muhammad; Winata, Devi Catur; Al Munawar, Ahmad (Physical Education Theory and Methodology, 2024)
Objectives. The study aimed to use a literature review methodology to ascertain the effect of regular exercise on cardiovascular health. Materials and methods. This review inquiry adhered to PRISMA guidelines for systematic reviews and meta-analyses. Studies had to be published between June 2022 and June 2024. The following search terms were used: (1) regular exercise; (2) cardiovascular health. This study’s data source was the Scopus search engine. Results. A total of six articles were identified from the 229 search results in the database that were modified to meet the specified requirements According to the results of this systematic review, regular exercise has a positive impact on cardiovascular health, reducing the incidence of morbidity and mortality, improving prognosis, and lowering the risk of heart disease. Conclusions. The findings indicate that the practice of regular exercise has been proven to have a beneficial effect on cardiovascular health. Thus, engaging in regular exercise can significantly enhance physical well-being and improve the cardiovascular condition.